Immigrants in Norway: Resilience, challenges and vulnerabilities in times of COVID-19 - Sanjana Arora; Bodil Bø; Ingrid Tjoflåt; Hande Eslen-Ziya (Elsevier, 2022)
Immigrants have been found to be disproportionately impacted during the COVID-19 pandemic across the world. Our study, exploring the experiences of immigrants in Norway during the pandemic, is based on interviews and focus group discussions with 10 and 21 immigrants, respectively. Our analysis showed that participants perceived the circumstances induced by the pandemic to be difficult and voiced the challenges experienced. Their experiences encompassed social, economic, and the public sphere, where immigrants felt themselves to be in more vulnerable positions than before the pandemic. Our analysis identified four main themes: 1) Feeling stagnated, 2) Perceptions towards government and health authorities, 3) Boundaries of us vs them, and 4) Coping. We conclude our paper by stating that government and health authorities should consider both short-term and long-term consequence of the pandemic to mitigate impact on communities at risk.